The Keloid Intervention Benefit Inventory 21: A New Assessment Tool for the Quality of Life of Patients with Auricular Keloids - Häussler, Daniel; Hüttemann, Stefanie; Weiß, Christel; Rotter, Nicole Karoline; Sadick, Haneen (Facial Plastic Surgery, 2021)
The assessment of the quality of life (QoL) of patients with chronic diseases before and after medical interventions has gained increasing importance in recent decades. Particularly for patients with visible keloid scars in the head and neck region, standardized measurement tools are either absent or have been shown to be insufficient. The aim of the present study was to create a new standardized questionnaire that is specific to auricular keloid patients and reflects their clinical symptoms and QoL. The Keloid Intervention Benefit Inventory 21 (KIBI-21) questionnaire was developed in two stages. First, a group of experts identified a pool of 26 questions and modified and supplemented the items through a comparison with existing QoL assessments so that they related to keloid-specific clinical symptoms and the QoL of patients with auricular keloids before and after a medical intervention. This questionnaire was distributed to 27 outpatients who had undergone medical interventions for visible auricular keloids. Second, a sequential statistical analysis was conducted. This included a single-item assessment and reduction, analysis for internal consistency, construct validity, and divergence validity as well as a factor analysis. The analyses were performed for the entire questionnaire and for the items in the subcategories General Health, Physical Symptoms, Self-Esteem, and Social Impact. The final version of this newly validated and standardized KIBI questionnaire consisted of 21 items, of which each item was assigned to only one subscale. The questionnaire showed a Cronbach's α of 0.84 with a good internal consistency. In the item correlation validity, strong associations were found in all subscales, except for the Social Impact Subscale. The keloid-specific QoL questionnaire KIBI-21 proved to be a reliable and reproducible instrument to assess the QoL and clinical symptoms in patients suffering from auricular keloids before and after a medical treatment.
Keywords: auricular keloids; quality of life (QoL); questionnaire; KIBI-21